Persepsi Mahasiswa Ilmu Komunikasi Universitas Muhammadiyah Makassar Terhadap Iklan “Temukan Makna Untuk Bersama” di Youtube IM3 - Andi Nur Firatunnizwah Akbar; Wardah; Ilham Riyadi (Jurnal Komunikasi dan Organisasi (J-KO), 2026)
This study was designed with the main objective of analyzing the perceptions of Communication Science students at Muhammadiyah University Makassar regarding the advertisement “Find Meaning Together” aired on YouTube IM3, with the main question: how do students interpret the message of the advertisement in relation to their experiences and values. This study uses a descriptive qualitative approach with the Stimulus–Organism–Response (S-O-R) theory as the basis for analysis, as well as data collection through in-depth interviews with selected informants. The results of the study show that the power of advertising lies not only in visual and audio elements, but also in narratives built with an emotional approach. These elements serve as stimuli that can foster emotional bonds in students (organisms), which in turn generate responses in the form of positive appreciation and encouragement to manifest real behavior in the form of small acts of kindness in everyday life. These findings reinforce the understanding that emotional approaches that are relevant to the lives of the younger generation are able to create psychological bonds that encourage audience engagement. In conclusion, this research makes a significant contribution to the study of digital marketing communication by emphasizing the importance of emotional storytelling that is in harmony with local culture. In addition, this research also opens up space for further exploration through a mixed-method approach or by expanding their search population, so that the external validity and generalization of the findings can be further strengthened.